NAVIGATING THE SOCIAL MEDIA ECOSYSTEM IN DIGITAL SEX WORK IN BRAZIL - Caminhas, Lorena (AoIR Selected Papers of Internet Research, 2026)
This paper examines how social media ecosystems have become fundamental workplaces for digital sex work, causing a series of ruptures and changes in the industry. Focusing on Brazilian erotic content creators. It explores how sex workers integrate multiple platforms to sustain their labour and how this ecosystem imposes new forms of governance that shape their working conditions. While social media facilitate visibility and audience-building, they also create structural imbalances, making success dependent on navigating platform policies and adapting to shifting moderation practices.Grounded in digital labour research and creator studies, the paper draws on ethnographic fieldwork (2021-2024) on Brazil’s most popular sex platforms—OnlyFans and Privacy—alongside social media (Instagram, Twitter, WhatsApp and Telegram). It also includes in-depth interviews with 16 erotic content creators, analysed using reflexive thematic analysis.Findings reveal that erotic creators strategically assemble a network of platforms, generating interdependent flows of content and audiences and forming a social media ecosystem central to their work. However, this ecosystem demands continuous adaptation and introduces precarious conditions, requiring creators to infer platform guidelines and constantly adapt to shifting moderation policies. Marginalised creators face heightened scrutiny, experiencing disproportionate content removals and account suspensions.Ultimately, the study argues that digital sex work is shaped by overlapping governance structures—those of social media, sex platforms, and broader regulatory forces—shaping its organisation and regulation. These findings highlight the need for further research into the implications of social media’s governance, particularly in marginalised labour sectors such as sex work.